In Vivo Efficacy and Metabolism of the Antimalarial Cycleanine and Improved In Vitro Antiplasmodial Activity of Semisynthetic Analogues - Uche, Fidelia Ijeoma (Antimicrob Agents Chemother, 2021)
Bisbenzylisoquinoline (BBIQ) alkaloids are a diverse group of natural products that demonstrate a range of biological activities. In this study, the in vitro antiplasmodial activity of three BBIQ alkaloids (cycleanine [compound 1], isochondodendrine [compound 2], and 2′-norcocsuline [compound 3]) isolated from the Triclisia subcordata Oliv. medicinal plant traditionally used for the treatment of malaria in Nigeria are studied alongside two semisynthetic analogues (compounds 4 and 5) of cycleanine. The antiproliferative effects against a chloroquine-resistant Plasmodium falciparum strain were determined using a SYBR green 1 fluorescence assay. The in vivo antimalarial activity of cycleanine is then investigated in suppressive, prophylactic, and curative murine malaria models after infection with a chloroquine-sensitive Plasmodium berghei strain. BBIQ alkaloids (compounds 1 to 5) exerted in vitro antiplasmodial activities with 50% inhibitory concentration (IC(50)) at low micromolar concentrations and the two semisynthetic cycleanine analogues showed an improved potency and selectivity compared to those of cycleanine. At oral doses of 25 and 50 mg/kg body weight of infected mice, cycleanine suppressed the levels of parasitemia and increased mean survival times significantly compared to those of the control groups. The metabolites and metabolic pathways of cycleanine were also studied using high-performance liquid chromatography–electrospray ionization–tandem mass spectrometry. Twelve novel metabolites were detected in rats after intragastric administration of cycleanine. The metabolic pathways of cycleanine were demonstrated to involve hydroxylation, dehydrogenation, and demethylation. Overall, these in vitro and in vivo results provide a basis for the future evaluation of cycleanine and its analogues as leads for further development.